Unveiling attitudes and dynamics - متیو اوموجمیت دامیلولا; الفینا نومابندلا سیشه (غالب)
.This theoretical inquiry explores stakeholder perspectives on queer community acceptance within rural Nigerian settings, focusing on Oye Ekiti, Ijan Ekiti, Irun Akoko, and Okiti Pupa. Employing a qualitative approach, the study uses interviews and content analysis grounded in Social Identity Theory to investigate attitudes and dynamics. Purposive sampling of 10-20 participants, including community leaders, queer individuals, NGO representatives, and general community members, provides insights into complex social interactions. The Thematic analysis highlights a tension between conservative resistance and emerging acceptance, influenced by religious doctrines, traditional values, and socio-economic factors. Despite significant opposition from religious and traditional leaders who view queer identities as incompatible with cultural norms, education and awareness efforts are contributing to gradual shifts in attitudes. Local NGOs face challenges in advocating for change amidst entrenched opposition. Recommendations include enhancing educational programs, strengthening NGO support, advocating for policy reform, fostering dialogue with community leaders, promoting positive media representation, addressing socio-economic barriers, and building coalitions to foster inclusivity.